Knowing the Salween River: Resource Politics of a Contested Transboundary River - Middleton, Carl.; Lamb, Vanessa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This open access book focuses on the Salween River, shared by China, Myanmar, and Thailand, that is increasingly at the heart of pressing regional development debates. The basin supports the livelihoods of over 10 million people, and within it there is great socio-economic, cultural and political diversity. The basin is witnessing intensifying dynamics of resource extraction, alongside large dam construction, conservation and development intervention, that is unfolding within a complex terrain of local, national and transnational governance. With a focus on the contested politics of water and associated resources in the Salween basin, this book offers a collection of empirical case studies that highlights local knowledge and perspectives. Given the paucity of grounded social science studies in this contested basin, this book provides conceptual insights at the intersection of resource governance, development, and politics of knowledge relevant to researchers, policy-makers and practitioners at a time when rapid change is underway. - Fills a significant knowledge gap on a major river in Southeast Asia, with empirical and conceptual contributions - Inter-disciplinary perspective and by a range of writers, including academics, policy-makers and civil society researchers, the majority from within Southeast Asia - New policy insights on a river at the cross-roads of a major political and development transition.
1.Introduction: Resources Politics and Knowing the Salween River -- 2.Salween: What$1 (Bs in a Name? -- 3.Hydropower Politics and Conflict on the Salween River -- 4.From Hydropower Construction to National Park Creation: Changing Pathways of the Nu River -- 5.Rites, Rights and Water Justice in Karen State: A Case Study of Community-based Water Governance and the Hatgyi Dam -- 6.Contested Water Governance in Myanmar/Burma: Politics, the Peace Negotiations and the Production of Scale -- 7.A State of Knowledge of the Salween River: An Overview of Civil Society Research -- 8.(3z(BWe Need One Natural River for the Next Genera-tion(3y(B: Intersectional Feminism and the Nujiang Dams Campaign in China -- 9.Local Context, National Law: The Rights of Karen People on the Salween River in Thailand -- 10.An Ethnobotanical Survey in Shan State, Myanmar: Where Thanlwin Biodiversity, Health, and Deforestation Meet -- 11.Not Only Anti-dam: Simplistic Rendering of Complex Salween Communities in their Negotiation for Development in Thailand -- 12.Powers of Access: Impacts on Resource Users and Researchers in Myanmar$1 (Bs Shan State -- 13.Fisheries and Socio-economic Change in the Thanlwin River Estuary in Mon and Kayin State, Myanmar -- 14.The Impact of Land cover changes on socio-economic conditions in Bawlakhe District, Kayah State -- 15.Local Knowledge and Rangeland Protection on the Tibetan Plateau: Lessons for Conservation and Co-management of the Upper Nu-Salween and Yellow River Watersheds -- 16.Future Trajectories: Five Short Concluding Reflections.s
Keywords: Physical geography; Water; Hydrology; Industrial management$1 (BEnvironmental aspects.s; Political sociology; Physical Geography; Water; Corporate Environmental Management; Political Sociology